- ENGLISH LITERACY MOVEMENT THROUGH FUN SHARED READING AT AISYIYAH KASIH IBU ORPHANAGE IN BENGKULU CITY: - - Nurcholis, Ivan Achmad (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
The students' ability to read, comprehend, and effectively use information in English is still a cause for concern. There are several factors exacerbating this situation. Apart from the very weak basic English proficiency, especially in reading skills which is the main issue, there is a lack of reading facilities in the community, and the interest and habit of reading have not taken root among the people. Observing this situation, there is a need for an initiative or movement to motivate and improve their English literacy skills. Thus, a community service activity was carried out. This activity took place at the Aisyiyah Kasih Ibu Orphanage in Bengkulu City and was attended by the children residing there. This activity aimed to launch a movement to enhance the literacy level of the students at the Aisyiyah Kasih Ibu Orphanage by implementing Fun Shared Reading. This activity spanned from 01 to 23 September 2023. The activities began with providing literacy materials in English, focusing on reading. After the reading session, discussions, related explanations, exercises, and creative activities related to the story were conducted. Through this community service, the foster children at the Aisyiyah Kasih Ibu Orphanage gained a new understanding and enthusiasm to improve their interest and habit in English literacy through the examples that were provided. Keywords: literacy movement, orphanage, fun shared reading